2013
DOI: 10.1093/infdis/jit409
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiology of Hepatitis E Virus Infection in an Urban Population in Zambia: Strong Association With HIV and Environmental Enteropathy

Abstract: Background. Hepatitis E virus (HEV) infection causes major epidemics of infectious hepatitis, with high mortality rates in pregnant women. Recent reports indicate that HEV coinfections with human immunodeficiency virus (HIV) may have a more protracted course. However, the impact of HEV infections in communities heavily affected by HIV remains poorly studied. We set out to examine age-related seroprevalence in a community where we have previously carried out studies on environmental enteropathy.Methods. Blood s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
28
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 24 publications
2
28
4
Order By: Relevance
“…It is recognized that HEV infections may pose serious threats to pregnant women and fetuses during pregnancy, resulting in congenital defects, spontaneous abortion and even death [Adjei et al, ; Goumba et al, ; Huang et al, ]. Similar to other recently‐published evidence [Singh et al, ; Purcell and Emerson, ; Jacobs et al, ], the present study showed that seroprevalence of HEV infection in the third trimester of pregnancy (18.7%) (95% CI 13.7%–23.4%) is higher than that in the second (15.5%) (95% CI 10.7%–20.3%) or the first trimester (15.3%) (95% CI 12.2%–18.4%) of pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…It is recognized that HEV infections may pose serious threats to pregnant women and fetuses during pregnancy, resulting in congenital defects, spontaneous abortion and even death [Adjei et al, ; Goumba et al, ; Huang et al, ]. Similar to other recently‐published evidence [Singh et al, ; Purcell and Emerson, ; Jacobs et al, ], the present study showed that seroprevalence of HEV infection in the third trimester of pregnancy (18.7%) (95% CI 13.7%–23.4%) is higher than that in the second (15.5%) (95% CI 10.7%–20.3%) or the first trimester (15.3%) (95% CI 12.2%–18.4%) of pregnancy.…”
Section: Discussionsupporting
confidence: 85%
“…The investigators hypothesized that alternative infectious agents may cause cross-reactivity of HEV EIAs, resulting in false positives. Other research has demonstrated EIA cross reactivity between EBV and CMV [1314], hepatitis A [15], and HIV [1617], suggesting a ‘molecular mimicry’ phenomenon. Our findings of a significant association between HIV and HEV IgM positivity, lack of HEV RNA, and lower rates of HEV EIA positivity among healthy control residents may be suggestive of such a process.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of HEV in the HIV‐infected population varies tremendously depending on the geographic area, from 1.5% to 70.5% . Furthermore, the clinical outcome whether HEV causes acute or chronic infection in HIV patients also differs among reported studies .…”
Section: Introductionmentioning
confidence: 99%